A review and perspective on control charting with image data. - Megahed, Fadel M. (Journal of Quality Technology)
Machine vision systems are increasingly being used in industrial applications due to their ability to provide not only dimensional information but also information on product geometry, surface defects, surface finish, and other product and process characteristics. There are a number of applications of control charts for these high dimensional image data to detect changes in process performance and to increase process efficiency. We review the control charts that have been proposed for use with image data in industry and in some medical device applications and discuss their advantages and disadvantages in some cases. In addition, we highlight some application opportunities available in the use of control charts with image data and provide some advice to practitioners.